THE INFLUENCE OF SOCIAL MEDIA ON MENTAL WELLBEING – A REVIEW OF LITERATURE - Natalia Pacocha,; Oliwia Gugała, (International Journal of Innovative Technologies in Social Science, 2024)
IntroductionCurrently, technological advancements have given most people unlimited access to social media. This has both many advantages and disadvantages. Social media significantly facilitate access to information and communication. However, social media can also negatively impact the mental health of the population. The aim of this study is to review the literature to discover the correlation between social media use and its impact on mental health.Materials and methodsA review of the literature available in the “PubMed” and „Google Scholar” databases was conducted. The search was performed by using the following keywords: social media use, fear of missing out, social media depression, depressive syndromes.ResultsUnrestricted access to social media has become an integral part of human life. This has led to improper use of social media, which can have detrimental effects on mental health. Specifically, it increases the risk of mood disorders, anxiety disorders, and depression. Moreover, it can lower self-esteem and life satisfaction. Additionally, it can foster the development of FOMO syndrome, which intensifies excessive social media use.ConclusionsFurther research on the impact of social media on mental health is crucial to discover effective methods of appropriate social media use. This will help in avoiding mental health disorders associated with social media use.